Inhibition of NKCC1 Modulates Alveolar Fluid Clearance and Inflammation in Ischemia-Reperfusion Lung Injury via TRAF6-Mediated Pathways - Shen, Chih-Hao; Lin, Jr-Yu; Chang, Yung-Lung; Wu, Shu-Yu; Peng, Chung-Kan; Wu, Chin-Pyng; Huang, Kun-Lun (Frontiers in Immunology, 2018)
Background: The expression of Na-K-2Cl cotransporter 1 (NKCC1) in the alveolar epithelium is responsible for fluid homeostasis in acute lung injury (ALI). Increasing evidence suggests that NKCC1 is associated with inflammation in ALI. We hypothesized that inhibiting NKCC1 would attenuate ALI after ischemia-reperfusion (IR) by modulating pathways that are mediated by tumor necrosis-associated factor 6 (TRAF6). Methods: IR-ALI was induced by producing 30 min of ischemia followed by 90 min of reperfusion in situ in an isolated and perfused rat lung model. The rats were randomly allotted into four groups comprising two control groups and two IR groups with and without bumetanide. Alveolar fluid clearance (AFC) was measured for each group. Mouse alveolar MLE-12 cells were cultured in control and hypoxia-reoxygenation (HR) conditions with or without bumetanide. Flow cytometry and transwell monolayer permeability assay were carried out for each group. Results: Bumetanide attenuated the activation of p-NKCC1 and lung edema after IR. In the HR model, bumetanide decreased the cellular volume and increased the transwell permeability. In contrast, bumetanide increased the expression of epithelial sodium channel (ENaC) via p38 mitogen-activated protein kinase (p38 MAPK), which attenuated the reduction of AFC after IR. Bumetanide also modulated lung inflammation via nuclear factor-κB (NF-κB). TRAF6, which is upstream of p38 MAPK and NF-κB, was attenuated by bumetanide after IR and HR. Conclusions: Inhibition of NKCC1 by bumetanide reciprocally modulated epithelial p38 MAPK and NF-κB via TRAF6 in IR-ALI. This interaction attenuated the reduction of AFC via upregulating ENaC expression and reduced lung inflammation.